TEACHING WRITING PERSONAL RECOUNT TEXT THROUGH THE STUDENTS’ PERSONAL PHOTOGRAPH AT THE EIGHTH GRADE OF JUNIOR HIGH SCHOOL 9 KENDARI - Has riati (Yayasan Akrab Pekanbaru, 2019)
The present study aimed to examine whether there was a significant effect of teaching writing personal recount text through the students’ personal photograph at the eighth grade of Junior High School 9 Kendari. The population of this study was the entire the eighth grade students of Junior High School 9 Kendari who enrolled in academic year 2012/2013. This research involved 34 students at class VIII5. The instrument of this research was writing text in recount genre. And the criteria of students’ writing were assessed from three aspects of writing composition, namely vocabulary, language use, and mechanic. The data were obtained from two essay writing tests. The data of the pre-test and post-test were analyzed through descriptive and inferential statistics. After the data were tested and found to be normal, the hypothesis was tested by using analysis of paired sample t-test. The result indicated that teaching writing personal recount text through the students’ personal photograph had a positive significant effect on students’ writing ability, especially on vocabulary aspect 70%, language use aspect 50%, and mechanics aspect 20%. It proved on mean of students’ final score was increased 19.5 from 57.41 in pre-test became 76.91 in post-test, the hypothesis testing was found that the probability value or (p value) was .000<0.05 or (p<0.05) and the calculation of tcount(13.893) was more than ttable (1.692) at the level significance (0.05) and (df) = 33. Therefore, it indicated that H0 was rejected and H1 was accepted. Therefore, it can be summed up that teaching writing through the students’ personal photograph had a positive effect at the eighth grade of Junior High School 9 Kendari.